Risk-oriented marketing strategies of international companies in FMCG sector - Пономаренко Тетяна Василівна (My University, 2024)
The relevance of the research topic is due to the need to create new producers in the sector of fast-moving consumer goods. Multinational brands take up more and more space on supermarket shelves each year. This hikes the competition, making it difficult to keep up. Recently, the world and the Ukrainian market have faced many challenges and risks due to force majeure obstacles. An in-depth study of this issue revealed the relevance of a multifactorial approach to building an effective risk-based marketing strategy. The dissertation analyses and explores the genesis of the modern concept of marketing strategies, the types of business risks in the FMCG sector and the adaptation of the marketing strategy in order to mitigate the impact of these risks. The scientific novelty of the study is solving a relevant scientific task, namely defining and outlining the necessary modern elements, tools and principles of marketing strategy for the effective and successful development of the company and its ability to compete with multinational companies. This task is investigated and solved under the lens of additional factors, such as the factor of riskiness of the environment where the company operates. Mechanisms of using marketing tools in the business of PP “KALYNTORG” and its TM MARIGOLD NATURAL have been examined from a scientific perspective. As part of the research, an innovative method for defining and implementing a marketing strategy yielded positive results. The comprehensive analysis carried out as part of the study showed a clear inadequacy of the existing approaches to the development of marketing strategies amidst the multifactorial riskiness of today’s consumer goods sector. Taking into account the results of the analysis of various practices of the marketing strategy development, the scientific task of developing the latest concept of forming an effective and successful marketing strategy for brands of the consumer goods sector, which is based on 4P and 4C in combination with the implementation of competitive strategies of Michael Porter, was solved as part of the dissertation research and the Blue Ocean Strategy by Renée Mauborgne and W. Chan Kim. This concept is also expanded by the innovative marketing toolkit of “interaction with distribution channels and trade networks”. The marketing strategy concept has been developed under the lens of the riskiness of the sector where the company is to operate. The strategy should be adapted in order to mitigate the negative effects for the brand in case of a risk event. The innovative concept developed is called FMCG Risk Marketing. The study consists of three main sections that comprehensively describe the determinants of marketing strategies from the perspective of practical use by brands in the consumer goods sector, namely: 1. Theoretical foundations of corporate marketing strategies have been considered; 2. Mechanics of adaptation of marketing strategies of brands to the modern risk profile of the consumer goods sector have been analyzed; 3. Level of the attractiveness of the Ukrainian market for international companies has been studied. The rapid internationalization of international brands of multinational companies in the consumer goods sector in recent decades, the COVID-19 pandemic and numerous military conflicts have showcased the relevance and necessity of developing effective marketing solutions for entering the market for new brands and maintaining the required level of sales for existing brands. The risks had to be identified and outlined in order to adapt the marketing strategy to them in advance. Therefore, successful brands focus more and more on the development of innovative marketing tools and risk-marketing systems that strengthen the strategic planning of the company as a whole, as well as improve the effectiveness of the response to the challenges to be faced. In order to explore the determinants of marketing strategies, the study carefully considers the description of “marketing tools” and their main components such as 4P (product, price, place, promotion), which is an integral part and the basis of any marketing strategy. Furthermore, the study examines the concept of 4C (cost, customer value, convenience, communication) in detail. The issue of consumer value of the product and its marginal utility is examined, as these factors directly affect the final price of the product. In addition, the study considers Michael Porter’s concept of competitive advantages: leadership and cost minimization strategy, differentiation strategy, focus strategy. It also explores Philip Kotler’s marketing strategies such as market leader strategy, challenger strategy, follower strategy and niche strategy. Great emphasis is placed on the issue of product differentiation, which was researched by Michael Porter, although the study approaches the differentiation from a more modern perspective, which was laid out by Renée Mauborgne and W. Chan Kim in their Blue Ocean theory. The dissertation substantiates the author’s concept of marketing strategy development – FMCG Risk Marketing. The implementation of the concept contributes to the sustainable development of the company’s brand and sales, effective competition due to pre-planned product and price strategies, confident market entry of the brand, its sustainable development, mitigation of negative effects due to the occurrence of risky events and the ability to keep balanced development in the framework of “marketing costs/the desired level of sales” and successfully overcome factors of global economic and geopolitical uncertainty, such as the COVID-19 pandemic and Russian military aggression against Ukraine. During 2021-2024, the results of the dissertation research were implemented in the development of the marketing strategy of Private Partnership “KALYNTORG”. PP “KALYNTORG” has been developing its brand TM MARIGOLD NATURAL from 2016. Among its main competitors are: Unilever, Colgate-Palmolive, Procter & Gamble. Based on the results of the study, the world leader in the production of beer, AB InBev Efes, was able to improve its performance. The company integrates the conclusions as well as recommendations of author regarding the effectiveness of different marketing activities within risky environment in order to elaborate its business strategy. The research helps the company to diminish negative risk’ consequences or eliminating them completely. The conclusions found by the author were taken into account during development the product planogram by LLC “EPICENTR K’, which is one of the biggest retail chains in Ukraine. Detailed analysis of the effectiveness of different types of sales in FMCG and a mathematical model constructed by the author enabled the company to increase its profitability within the skin-care product category by planning its promotions.

Актуальність теми дослідження продиктована необхідністю створення нових виробничих підприємств в Україні в сфері ринку товарів повсякденного попиту. Бренди багатонаціональних компаній з кожним роком займають все більше торгової площі на полицях супермаркетів. Відтак, конкуренція стає все більш складною. Протягом останніх років, світ та ринок України зіткнулися з багатьма викликами та ризиками, пов’язаними з настанням форс-мажорних обставин. У ході поглибленого вивчення даного питання, актуальним стає багатофакторний підхід для побудови дієвої маркетингової стратегії. В дисертації розглянута та досліджена генеза сучасної концепції маркетингових стратегій, типи ризиків економічної діяльності на ринку товарів повсякденного попиту та адаптація маркетингової стратегії з метою пом’якшення впливу таких ризиків. Наукова новизна дослідження полягає у вирішенні актуального наукового завдання, а саме – визначення та окреслення необхідних сучасних елементів, інструментів та засад маркетингової стратегії для ефективного та успішного розвитку компанії та її спроможності конкурування з багатонаціональними компаніями. Дане завдання вирішується з урахуванням додаткових факторів, а саме чинників ризикогенності середовища, у якому компанія веде свою економічну діяльність. Досліджено механізми використання інструментів маркетингу в економічній діяльності компанії ПП «Калинторг» та її бренду MARIGOLD NATURAL. В рамках дослідження застосовано інноваційний метод до визначення та втілення маркетингової стратегії. Проведений, в рамках дослідження, комплексний аналіз чітко показав недостатність вже існуючих підходів до формування маркетингових стратегій в сучасних умовах багатофакторної ризикогенності ринку товарів повсякденного попиту. Враховуючи зазначені результати проведеного аналізу різних практик формування маркетингових стратегій, в рамках дисертаційного дослідження вирішене наукове завдання з розробки новітньої концепції формування ефективної та успішної маркетингової стратегії для брендів ринку товарів повсякденного попиту, яка приймає за основу методологію 4P (product, price, place, promotion) та 4С (cost, customer value, convenience, communication) у поєднанні з методологією конкурентних стратегій Майкла Портера та стратегії «блакитного океану» Рене Моборна та В. Чан Кіма. До даної концепції окремо додається такий інноваційний інструментарій маркетингу, як «взаємодія з каналами дистрибуції та торговельними мережами». Розробка концепції маркетингової стратегії відбувається під призмою дослідження ризикогенності саме того ринку, де компанія планує вести свою операційну діяльність. Стратегія має бути адаптована з метою максимального пом’якшення негативного ефекту для бренду за умови настання ризикового випадку. Розроблена новітня концепція отримала авторську назву «ризик-маркетинг FMCG». Дослідження складається з трьох основних розділів, які всебічно описують детермінанти маркетингових стратегій з практичної точки зору брендів ринку товарів повсякденного попиту, а саме: 1. розглянуті теоретичні основи корпоративних маркетингових стратегій; 2. проаналізовані механізми адаптації маркетингових стратегій брендів до сучасного ризикового профілю ринку товарів щоденного попиту; 3. досліджений рівень привабливості ринку України для міжнародних компаній. Стрімка інтернаціоналізація міжнародних брендів багатонаціональних компаній ринку товарів повсякденного попиту останніх десятиліть, пандемія СOVID 2019 та чисельні військові конфлікти підкреслили актуальність та необхідність розробки ефективних маркетингових рішень для виходу на ринок нових брендів та втримання необхідного рівня продажів для вже існуючих брендів. Виникла потреба у ідентифікації та окресленні ризиків для адаптації маркетингової стратегії до них заздалегідь. Відтак, успішні бренди приділяють все більшої уваги розвитку інноваційних маркетингових інструментів та систем ризик-маркетингу, які посилюють стратегічне планування компанії в цілому, та підвищують ефективність реакції на виклики, з якими доводиться зіткатися. З метою дослідження детермінант маркетингових стратегій ретельно розглянуто описання «інструментарію маркетингу» та таких основних складових як 4P (product, price, place, promotion), що є невід’ємною частиною та основою будь-якої маркетингової стратегії. Також, в дослідженні детально розглянута концепція 4С (cost, customer value, convenience, communication). Ретельно вивчається питання споживчої вартості товару та його граничної корисності, так як ці фактори безпосередньо впливають на кінцеву ціну товару. На додаток до цього розглядається концепція конкурентних переваг Майкла Портера: стратегія лідерства та мінімізації витрат, стратегія диференціації, стратегія фокусування. Досліджуються маркетингові стратегії Філіпа Котлера, а саме: стратегія «лідера» ринку, стратегія «челенджера», стратегія «послідовника» та стратегія «нішера». Велика увага приділяється питанню диференціації товару, яке досліджувалося Майклом Портером, але диференціація розглядається автором через призму новітньої теорії «блакитного океану» Рене Моборна та В. Чан Кіма. В дисертації обґрунтована авторська концепція формування маркетингової стратегії «ризик-маркетинг FMCG». Реалізація концепції сприяє сталому розвитку бренду компанії та продажів, ефективній конкурентній боротьбі завдяки завчасно спланованим стратегіям товару та ціни, впевненого входження бренду на ринок, сталого його розвитку, зменшення негативних наслідків через настання ризикових подій та здатності тримати збалансований розвиток в системі координат «витрати на маркетинг – бажаний рівень продажів» та успішно протистояти чинникам світогосподарської та геополітичної невизначеності, як наприклад пандемія COVID 19 та російська військова агресія проти України. Протягом 2021-2024 років результати дисертаційного дослідження було впроваджено в побудову маркетингової стратегії компанії ПП «Калинторг». Компанія ПП «Калинторг» розвиває власний національний бренд TM MARIGOLD NATURAL з 2016р, основними конкурентами якого є Unilever, Colgate-Palmolive, Procter & Gamble. За результатами дослідження було вдосконалено роботу компанії – світового лідера у виробництві пива AB InBev Efes. Компанія інтегрує висновки та рекомендації дослідження автора стосовно торгової діяльності в умовах ризикового середовища у розробку подальшої стратегії свого розвитку. Це дозволяє компанії допомогти пом’якшити потенційні ризики або повністю їх уникнути завдяки адаптації своєї стратегії. Висновки, до яких прийшов автор, були враховані при розробці товарної планограми однієї з найбільших торгових мереж України – ТОВ «Епіцентр К». Ретельний аналіз ефективності проведення цінових акцій та побудована автором математична модель, дозволили компанії «Епіцентр К» спланувати маркетингові заходи у мережі таким чином, щоб збільшити загальну прибутковість полиці категорії товарів «засоби догляду за шкірою».
Ризик орієнтовані маркетингові стратегії міжнародних компаній на ринку товарів повсякденного попиту
Keywords: маркетингові стратегії; міжнародні компанії; ризик; ринок товарів повсякденного попиту; поведінка споживачів; конкуренція; цифровий маркетинг; брендинг; канали дистрибуції; конкурентні переваги; маркетинговий інструментарій; міжнародна конкурентоспроможність; інноваційний розвиток; глобальні проблеми; marketing strategies; international companies; risk; FMCG (fast-moving consumer goods); consumer behavior; competition; digital marketing; branding; distribution channels; competitive advantages; marketing instruments; international competitiveness; innovative development; global problems